1990
DOI: 10.1016/1044-0305(90)80003-6
|View full text |Cite
|
Sign up to set email alerts
|

Internal energy distributions deposited in doubly and singly charged tungsten hexacarbonyl ions generated by charge stripping, electron impact, and charge exchange

Abstract: The distribution Pε of internal energies deposited in W(CO)6 (+•). ions upon charge stripping (that is, electron detachment to yield the doubly charged ion in the course of a single kiloelec-tronvolt energy collision) was estimated by a thermochemical method from the measured relative abundances of the doubly charged fragment ions produced. The thermochemical information needed to estimate P/ge was obtained by measuring the threshold translational energy losses associated with charge stripping of the singly ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 26 publications
(12 reference statements)
2
53
0
Order By: Relevance
“…Because the dissociation energy needed to lose CO molecules is well known, the number of CO units lost from the molecular ion brackets the internal energy (Kenttamaa & Cooks, 1985;Wysocki, Kenttamaa, & Cooks, 1987;Cooks et al, 1990). Although very useful and valuable, metal carbonyls have a chemical structure that is dissimilar to most organics, so they might behave differently in mass spectrometry.…”
Section: Leucine Enkephalin As a Thermometer Molecule -The Use Ofmentioning
confidence: 98%
See 1 more Smart Citation
“…Because the dissociation energy needed to lose CO molecules is well known, the number of CO units lost from the molecular ion brackets the internal energy (Kenttamaa & Cooks, 1985;Wysocki, Kenttamaa, & Cooks, 1987;Cooks et al, 1990). Although very useful and valuable, metal carbonyls have a chemical structure that is dissimilar to most organics, so they might behave differently in mass spectrometry.…”
Section: Leucine Enkephalin As a Thermometer Molecule -The Use Ofmentioning
confidence: 98%
“…Thermometer molecules are often used in mass spectrometrythe original idea goes back to the 1960s, to studies on energy dependence (Vekey, Brenton, & Beynon, 1986), and which has been developed further by Cooks and other researchers (Williams & Cooks, 1968;Kenttamaa & Cooks, 1985;Vekey, Brenton, & Beynon, 1986;Wysocki, Kenttamaa, & Cooks, 1987;Cooks et al, 1990;De Pauw, Pelzer, & Natalis, 1990;Derwa, De Pauw, & Natalis, 1991;Vekey, Somogyi, & Wysocki, 1995). The main idea is to use a compound that has a simple fragmentation pattern with known dissociation energetics.…”
Section: Leucine Enkephalin As a Thermometer Molecule -The Use Ofmentioning
confidence: 99%
“…Whereas doubly-charged fragment ions resulting from CAD were dominant in the CID spectrum with the Xe target, singly-charged fragment ions result- 35) ing from ETD were dominant in the CID spectrum with the Cs target. e most intense peak resulting from ETD was estimated to be associated with a charge reduced ion in which H 2 had been abstracted from the precursor.…”
Section: He-etd Of Peptides With Post-translational Modificationsmentioning
confidence: 99%
“…Using the same method, Cooks and coworkers determined the internal energy distributions, P(ε), in doubly charged ions following electron transfer in high-energy collisions by using a sector-type mass spectrometer and in low-energy collisions by using a triple quadrupole mass spectrometer with various atomic and molecular targets. 35) Di erences between the deposition of internal energy induced by collisional activation and electron transfer were investigated using W(CO) 6 2+ ions on collision with a rare gas and with an alkali metal target. 36,37) e internal energy deposition in collisionally activated dissociation (CAD) evaluated with a rare gas target was broad and decreased with increasing internal energy.…”
Section: Introductionmentioning
confidence: 99%
“…Wysocki et al [20] have reported the use of so-called thermometer molecules to measure internal energy distributions P(ε) of gas-phase ions. By using the same method, Cooks and coworkers determined the internal energy distributions, P(ε), in doubly charged ions following electron transfer in high-energy collisions by using a sector-type mass spectrometer and in lowenergy collisions by using a triple quadrupole mass spectrometer with various atomic and molecular targets [21][22][23]. One of the authors have previously measured the internal energy distribution of neutral species formed through neutralization in charge-inversion mass spectrometry with alkali metal targets by using the thermometer molecule W(CO) 6 [24].…”
Section: Introductionmentioning
confidence: 99%